Christian-Islamic Relations in Medieval and Modern History: Tracing the Roots of Revitalization Toward Tolerance - Tekeng, Abbas (Pascasarjana IAIN Sultan Amai Gorontalo, 2024)
This paper aims to trace the roots of revitalization in the effort towards tolerance of Islamic and Christian relations in medieval to modern history. The method used is literature with a historical analysis approach. The results are: (1) the history of Islamic and Christian relations is very harmonious and even a strong friendship. This lasted until the caliphate of Bani Umayyah and Bani Abbasiyah reached its golden peak; (2) the tension between Islam and Christianity began to heat up when the caliphate of Bani Abbasiyah experienced a decline in the Middle Ages. In addition to the polemical and apologetic nature of the debate between Islamic and Christian leaders due to the expansion of the Islamic caliphate and the strengthening of the internal cohesion of the Christian world that encouraged Islamic and Christian rivalry, a series of Crusades also took place. This polemic gave birth to debates in which each side attacked and proved the advantages and beauty of its own religion and showed the weaknesses and ugliness of other religions; (3) the main cause of conflict between Islam and Christianity is not because the core teachings of the religion itself are intolerant and exclusive, but more determined and conditioned by the historical-economic-political situation surrounding Muslim communities in various places. This is where the importance of dialog that prioritizes the principle of equality, and brotherhood that upholds tolerance between religious communities as shown by the Prophet Muhammad Saw.